2016
DOI: 10.1093/nar/gkw121
|View full text |Cite
|
Sign up to set email alerts
|

The human DNA ends proteome uncovers an unexpected entanglement of functional pathways

Abstract: DNA ends get exposed in cells upon either normal or dysfunctional cellular processes or molecular events. Telomeres need to be protected by the shelterin complex to avoid junctions occurring between chromosomes while failing topoisomerases or clustered DNA damage processing may produce double-strand breaks, thus requiring swift repair to avoid cell death. The rigorous study of the great many proteins involved in the maintenance of DNA integrity is a challenging task because of the innumerous unspecific electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…In addition to these DNA repair and DNA replication‐associated proteins, a number of proteins belonging to the family of Dynamins, involved in the cytoskeleton dynamics, are specifically recruited onto the substrate. A similar result has already been noticed in a proteomic study of DNA‐ends specific proteins, [ 13 ] but the functional relevance of this unexpected association awaits further investigations. Finally, some heterogeneous nuclear ribonucleoproteins were recovered that reflects their ability to bind to ssDNA with high affinity.…”
Section: Resultssupporting
confidence: 83%
“…In addition to these DNA repair and DNA replication‐associated proteins, a number of proteins belonging to the family of Dynamins, involved in the cytoskeleton dynamics, are specifically recruited onto the substrate. A similar result has already been noticed in a proteomic study of DNA‐ends specific proteins, [ 13 ] but the functional relevance of this unexpected association awaits further investigations. Finally, some heterogeneous nuclear ribonucleoproteins were recovered that reflects their ability to bind to ssDNA with high affinity.…”
Section: Resultssupporting
confidence: 83%
“…However, the mechanism that underlays MRN-dependent accumulation of RNAPII at DSBs remains elusive. RNAPII components were also detected as DNA end-binding proteins by mass spectrometry (73). The majority of DSBs in asynchronous cells are repaired by non-homologous end joining (NHEJ), which involves minimal resection by Mre11 3′-5′exonuclease (74,75).…”
Section: Discussionmentioning
confidence: 99%
“…We found most of these in TRF2 immunoprecipitates. Berthelot et al also previously identified glyceraldehyde-3-phosphate dehydrogenase as a telomere associated factor using affinity chromatography based on capture by telomeric oligonucleotides [57].…”
Section: Discussionmentioning
confidence: 99%